Methylmalonate-Semialdehyde Dehydrogenase Deficiency With Cardiac Presentation: A Case Report With Literature Review - Morteza Alijanpour Aghamaleki; Masoomeh Rezapour; Kazem Babazadeh; Hassan Zamani; Faeze Aghajanpour (Mazandaran University of Medical Sciences, 2019)
Background: Methylmalonate-semialdehyde Dehydrogenase Deficiency (MMSDHD) is an uncommon autosomal recessive disorder. MMSDH is an enzyme encoded by the protein coding gene ALDH6A1 in humans. Case Presentation: We present a 4-year-old boy with elevated liver enzymes, 3-hydroxyisobutyric aciduria (MMSDHD) and cardiac symptoms. He had a mutated ALDH6A1 gene, c.184c>G (p.Pro62Ala). Conclusions: This is one of the rare case reports in the world and the first one in Iran that reports MMSDHD with cardiac disease.